Morphological studies and molecular data on a new marine ciliate, Apokeronopsis sinica n. sp. (Ciliophora: Urostylida), from the South China Sea - Liu, Weiwei; Li, Jiqiu; Gao, Shan; Shao, Chen; Gong, Jun; Lin, Xiaofeng; Liu, Hongbin; Song, Weibo (Zootaxa, 2009)
The morphology of a new marine urostylid ciliate, Apokeronopsis sinica n. sp., collected from the Clear Water Bay, Hong Kong, was investigated. Additionally, the SSrRNA gene was sequenced in order to make a comparison at molecular level. Based on both morphological and molecular data, descriptions and comparisons with its congeners are provided. Apokeronopsis sinica is characterized by: body size about 150–200 × 50–65 µm in vivo; two kinds of cortical granules; about 20 cirri in frontal area which form the non-typical bicorona; 2 frontoterminal, ca. 4 buccal and 10 transverse cirri; midventral complex consists of 21–32 pairs of cirri; on average 35 right and 30 left marginal cirri; about 50 membranelles; invariably 3 dorsal kineties. A key to the identification of the known Apokeronopsis species was suggested. The small subunit rRNA gene sequence differences between Apokeronopsis sinica and its congeners range from 1.64% to 3.72%.